On the compressibility of liquid metals. (June 2017) - Marcus, Yizhak
Highlights: The adiabatic compressibilities of 64 liquid metals are presented. The isothermal compressibilities of 64 liquid metals are presented. The constant volume heat capacities of liquid metals are presented. The product of the compressibility and surface tension of liquid metals is discussed. Abstract: The adiabatic compressibilities κ S of 64 liquid metallic elements at their melting points were obtained from the densities ρ and speeds of sound u reported in the literature. The isothermal compressibilities were obtained from the κ S values by means of the molar volumes V, isobaric expansibilities α P, and isobaric molar heat capacities C P from the literature. The ratios γ  =  κ T / κ S  =  C P / C V yielded the isochoric molar heat capacities C V . The products κ T σ, using surface tension data from the literature, were calculated and shown to diminish linearly with increasing cohesive energy densities.